THE EFFECTS OF UTILIZING GEOTHERMAL ENERGY IN THERMAL POWER PLANTS ON THE PLANT PERFORMANCE AND FUEL SAVING - Ahmet DAĞDAŞ (Pamukkale University Journal of Engineering Sciences, 2006)
The share of electricity production from thermal power plants for Turkey is about 61 %. Since the fossil fuels are rapidly consumed, the concept of fossil fuel saving is very important for humanity. In this paper, the effects of boiler feed water preheating by means of geothermal brine on overall performance and fossil fuel savings in thermal power plants are examined. According to the performed analysis, power plant thermal efficiency could be increased of 2-4 % via geothermal preheating. In this analysis, a hypothetical thermal power plant is considered and its performance is evaluated. According to analysis, 1 million US$ in fossil fuel savings and 4.1 % increase in thermal efficiency could be achieved by the use of geothermal preheating.